(3cJGH aj GdeMGVQGJs
(3ChdgG (B:s
(3GdMeO ddg GdeWdY Ydi eUjQ GdGehQ heBHgG GdHGH GdQGHY YTQ ai GdeThQI hGdQCi s
(3BNQgG (B:s
(3cGf GdeZjQI Hf YHO GdQMef Hf GdMGQK Hf gTGe jWYe GdWYGe bGd Gf GdOLGd dGJUGH Yjfg ai SHjd Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs